THE ENHANCEMENT OF COMMUNICATION SKILL AND MASTERY OF THE MATERIAL CONCEPT IN CHEMICAL EQUILIBRIUM WITH LEARNING CYCLE 5E MODEL - dewi natas haning tias tuti; ratu betta rudibyani; emmawaty sofya (Universitas Lampung, 2012)
This research aimed to describe the effectiveness of LC 5E learning model in improving skill to communicate and mastery of the concept of chemical equilibrium the student. The population in this study were all students of class XI IPA in State Senior High School 6 Bandar Lampung school year 2012-2013 and spread into three classes namely XI IPA1, IPA2 XI, and XI IPA3. Sampling was done by purposive sampling technique. The sample in this reseach was a class XI IPA2 as experimental class the applied to LC 5E learning model and a class XI IPA3 as class control the applied to conventional learning. This is a quasi-experimental research using Non Equivalent (Pretest and Posttest) Control Group Design. Data analysis in this research using the n-Gain and t-test. The results showed the value average of n-Gain skills communicate for the experimental class of 0,77 (high category) while the control class 0,57 (medium category) and the mastery of concepts for a class experiment of 0,36 (medium category) while the control class 0,25 (low category). Based on t test, obtained skill to communicate the resulted thitung = 4.617 ttabel = 1.67. This means that skill to communicate classes with learning LC 5E higher than conventional the class with learning. Mastery of concepts resulted thitung = 2.8178 ttabel = 1.67. It can be concluded that learning LC 5E effective in improving the skill to communicate and mastery of concepts chemical equilibrium the students. Keywords : LC5E, skill to comunicate, mastery of the concept